An Updated Review of Recent Advances in Neurosyphilis - Zhou, Jia; Zhang, Hanlin; Tang, Keyun; Liu, Runzhu; Li, Jun (Frontiers in Medicine, 2022)
Neurosyphilis is caused by Treponema pallidum invading the central nervous system, of which the incidence is increasing worldwide. Due to its variable clinical manifestations, diagnosis of neurosyphilis remains challenging, especially the asymptomatic form. This review focuses on recent advances in neurosyphilis, including epidemiology, clinical manifestations, laboratory findings, comorbidities, diagnosis, treatment, prognosis, and basic research. The expansion of men who have sex with men and the infection of human immunodeficiency virus mainly accounted for the increasing incidence of neurosyphilis. The rate of some historically described forms of neurosyphilis in the pre-antibiotic era declined significantly; atypical features are more prevalent. Neurosyphilis, regarded as a great mimicker for neuro-ophthalmic, audio-vestibular, and psychiatric disorders, often presents concomitantly with other diseases, including metabolic disorders. Studies on long non-coding RNAs, miRNAs, chemokines, and metabolites in peripheral blood and cerebrospinal fluid may facilitate exploring the pathogenesis and identifying novel biomarkers of neurosyphilis. The drug resistance of Treponema pallidum to penicillin has not been reported; ceftriaxone was proposed to be more effective than penicillin, whereas few randomized controlled trials supported this view. This study may pave the way for further research, especially the diagnosis and treatment of neurosyphilis.